DETERMINANTS OF IPO UNDERPRICING: VALUATION, PERFORMANCE, AND NON-FINANCIAL FACTORS - Ali Mutasowifin (COMPETITIVE, 2025)
Underpricing continues to be a prevalent phenomenon in Indonesia’s initial public offerings (IPOs), where issuing firms often fail to obtain the fair market value of their shares. This study is highly relevant given that, from 2012 to 2022, 92% of 415 IPOs listed on the Indonesia Stock Exchange (IDX) experienced underpricing. The purpose of this research is to examine the determinants of IPO underpricing through stock valuation, financial performance, and non-financial factors. Employing a quantitative method with multiple linear regression analysis, the study analyzes 259 non-financial companies using six independent variables: Price to Book Value (PBV), Price to Earnings Ratio (PER), Debt to Equity Ratio (DER), Return on Equity (ROE), Underwriter Reputation (UDW), and Auditor Reputation (AUD). The results show that PBV (β = –0.007; p < 0.05) and UDW (β = –0.071; p < 0.05) significantly and negatively affect underpricing, while PER (β = 0.0001; p < 0.05) has a significant positive impact. Meanwhile, DER, ROE, and AUD have no significant effects. These findings indicate that firm valuation accuracy and reputable underwriters play vital roles in mitigating underpricing. Strengthening these aspects can enhance market efficiency and investor confidence in Indonesia’s IPO market